2001
DOI: 10.1002/jgm.187
|View full text |Cite
|
Sign up to set email alerts
|

Different behavior of branched and linear polyethylenimine for gene deliveryin vitro andin vivo

Abstract: Branched and linear PEI/DNA complexes differ in their ability to transfect cells. The greater efficiency of linear PEI might be due to an inherent kinetic instability under salt conditions. Understanding how to employ this kinetic instability of linear PEI could help in designing future vectors with greater flexibility and transfection efficiency in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
512
0
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 660 publications
(544 citation statements)
references
References 28 publications
27
512
0
5
Order By: Relevance
“…An exception to this is delivery to the lung, where it has been shown that large aggregating PEI/DNA particles passively target the lung following tail-vein injection. 23,24 For receptor-specific endocytosis, ligands such as epidermal growth factor (EGF) 25 and RGD peptide 26 have been utilized to increase cell specificity and overall uptake in vitro and in vivo. Though targeting often increases transfection, some experiments show that uptake that is both specific and efficient only occurs at a narrow window of charge ratios or not at all.…”
Section: Designing Polymeric Nanoparticles For Increased Uptake and Lmentioning
confidence: 99%
“…An exception to this is delivery to the lung, where it has been shown that large aggregating PEI/DNA particles passively target the lung following tail-vein injection. 23,24 For receptor-specific endocytosis, ligands such as epidermal growth factor (EGF) 25 and RGD peptide 26 have been utilized to increase cell specificity and overall uptake in vitro and in vivo. Though targeting often increases transfection, some experiments show that uptake that is both specific and efficient only occurs at a narrow window of charge ratios or not at all.…”
Section: Designing Polymeric Nanoparticles For Increased Uptake and Lmentioning
confidence: 99%
“…We still do not have reasonable explanation for this discrepancy as is sometimes observed for non-viral vector systems such as polyethylenimine. 35 Presumably, primary liver cells and lined HepG2 cells may have different cellular metabolism. Furthermore, in vitro cell culture condition has quite different circumstances from in vivo.…”
Section: Gene Therapymentioning
confidence: 99%
“…Linear PEI appears to assist these transport processes, whereas branched PEI and most nonviral delivery systems do not. 3,30 Other methods of assisting plasmid transport to the nucleus include the use of nuclear localization signal peptides. 31 It is possible that in the case of ODS, SPM directs the complex toward the cell nucleus.…”
Section: Intracellular Traffickingmentioning
confidence: 99%
“…The cultured cells were transfected with labeled plasmid (pGeneGrip) and unlabeled ODS or transfected with unlabeled plasmid and labeled ODS according to the transfection protocol above. At the appropriate time points (30,60,90,120, and 240 min), the cell culture was washed 3 times with sterile PBS and the confocal analysis was performed on the sample of living cells in sterile PBS. The images described in Figure 6 represent the behavior observed for 450% of the cells in every well (four wells for each treatment).…”
Section: Confocal Fluorescence Imaging Microscopymentioning
confidence: 99%